About Ahmad Hazini and his religious works - Kydyr, Т Е; Tulakbaeva, K Zh. (Journal of Oriental Studies, 2016)
The article discusses the importance of the work Ahmad Hazini in sufian ideas Khwaja Ahmad Yasawi.